New pioglitazone metabolites and absence of opened-ring metabolites in new n-substituted thiazolidinedione - Campos, Michel Leandro; Cerqueira, Letícia Bonancio; Silva, Bruna Cristina Ulian [UNESP]; Franchin, Taísa Busaranho [UNESP]; Galdino-Pitta, Marina Rocha; Pitta, Ivan Rocha; Peccinini, Rosângela Gonçalves [UNESP]; Pontarolo, Roberto (Elsevier, 2018)
Thiazolidinediones (TZDs) are drugs used to treat type 2 diabetes mellitus; however, several safety concerns remain regarding the available drugs in this class. Therefore, the search for new TZD candidates is ongoing; metabolism studies play a crucial step in the development of new candidates. Pioglitazone, one of the most commonly used TZDs, and GQ-11, a new N-substituted TZD, were investigated in terms of their metabolic activity in rat and human liver microsomes to assess their metabolic stability and investigate their metabolites. Methods for preparation of samples were based on liquid-liquid extraction and protein precipitation. Quantitation was performed using liquid chromatography (LC)-tandem mass spectrometry, and the metabolite investigation was performed using ultraperformance LC coupled to a hybrid quadrupole-time of flight mass spectrometer. The predicted intrinsic clearance of GQ-11 was 70.3 and 46.1 ml/kg per minute for rats and humans, respectively. The predicted intrinsic clearance of pioglitazone was 24.1 and 15.9 ml/kg per minute for rats and humans, respectively. The pioglitazone metabolite investigation revealed two unpublished metabolites (M-D and M-A). M-A is a hydration product and may be related to the mechanism of ring opening and the toxicity of pioglitazone. The metabolites of GQ-11 are products of oxidation; no ring-opening metabolite was observed for GQ-11. In conclusion, under the same experimental conditions, a ring-opening metabolite was observed only for pioglitazone. The resistance of GQ-11 to the ring opening is probably related to N-substitution in the TZD ring.